TINJAUAN RISIKO, MODAL DAN PROFITABILITAS PERBANKAN - Pratiwi, Lia; Sihono, Agus (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2024)
This research aims to determine the analysis of risk and bank capital on bank profitability. This research uses secondary data with the type of causality research. The population in this research is banking conventional companies registered on the Indonesia Stock Exchange (IDX) with the observation year 2020-2022, using financial report data from 31 banks for 3 years of observation. The sampling technique used in this research is purposive sampling technique. The research results show that, simultaneously credit risk, liquidity risk, market risk and bank capital influence bank profitability. Partially, credit risk has a significant negative effect on bank profitability and market risk has a significant positive effect on bank profitability. Meanwhile, liquidity risk and bank capital do not have a significant effect on the profitability of banking companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This research results provide implications for the importance of bank’s compliance with Bank Indonesia or Financial Services Authority regulations, because this will affect profitability.Keywords: Credit Risk; Liquidity Risk; Market Risk; Bank Capital; Profitability.